2011
DOI: 10.1002/smll.201102009
|View full text |Cite
|
Sign up to set email alerts
|

3D Self‐Assembled Plasmonic Superstructures of Gold Nanospheres: Synthesis and Characterization at the Single‐Particle Level

Abstract: The synthesis of 3D self-assembled plasmonic superstructures of gold nanospheres as well as the characterization of their structural and optical properties at the single-particle level is presented. This experimental work is complemented by FEM (finite element method) simulations of elastic scattering spectra and the spatial |E|(4) distribution for establishing structure-activity correlations in these complex 3D nanoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 43 publications
2
74
0
2
Order By: Relevance
“…This will be discussed in detail in §4. Nanoassemblies with multiple hot spots have also been fabricated according to colloidal chemistry reported by Schlü cker's group [73]. The electromagnetic field and the EF around the nanoassemblies were simulated and calculated by the finite-element method, which indicated that the EF value on the nanoassemblies can be as high as 10 10 , demonstrating its potential to be used as a SERS substrate for SM sensing.…”
Section: Nanostructures For Single-molecule Surface-enhanced Raman Spmentioning
confidence: 99%
“…This will be discussed in detail in §4. Nanoassemblies with multiple hot spots have also been fabricated according to colloidal chemistry reported by Schlü cker's group [73]. The electromagnetic field and the EF around the nanoassemblies were simulated and calculated by the finite-element method, which indicated that the EF value on the nanoassemblies can be as high as 10 10 , demonstrating its potential to be used as a SERS substrate for SM sensing.…”
Section: Nanostructures For Single-molecule Surface-enhanced Raman Spmentioning
confidence: 99%
“…In order to overcome this limitation, an alternative approach to reliably engineer 3D SERS substrates 7 approaches, is an emerging and promising field for high-yield production of 3D NP clusters with small interparticle gaps. [28] Many methods have been reported to produce 3D organized plasmonic clusters with high coordination number by the use of nucleic acids or other organic molecules as linking elements. Au NPs with identical sizes but different shapes have been used as building blocks to prepare 3D superstructures.…”
Section: Page 5 Of 35mentioning
confidence: 99%
“…25 Hence, only electrostatically assembled 3D core-satellite superstructures have been fully characterized on a substrate, although these structures are highly asymmetric due to the random distribution of the satellite particles on the core. 26 We report here the first synthesis and optical studies of the plasmon modes of highly ordered 3D gold tetrahedra, pentamers and hexamers. The assembled structures are found to be stable on substrates in stark contrast to earlier clusters and can be visualized using scanning electron microscopy (SEM) and atomic force microscopy (AFM).…”
mentioning
confidence: 99%